Direito a informação arquivística governamental via web nos municípios do Estado do Pará - LOPES, Paula Suellen Correa Padilha (2017)
The present work was developed around the investigation of how government archival information is disseminated through the use of the Internet, aiming at the precepts of the applicability of the Law on Access to Information. This study has relevance to scientific and social issues, so that the impact of the Law on Access to Information in the Northern Region of Brazil, specifically in the state of Pará, can be observed. Its general objective is to analyze the applicability of the Law Access to Information and the availability of governmental archival information on the city hall of the municipalities of the state of Pará. For the development of the research was elaborated a checklist, with fourteen items, that should be followed by public bodies and institutions for a good practice of Public transparency via web-access, using the technique of systematic observation, so that the data collection is performed by the researcher himself, before the use of pre-established techniques for observation. Public information via the web-access provides the citizen with real-time power to supervise government accounts, however it is necessary that this information is made available in a satisfactory and efficient way, so that it can meet the needs sought by the citizen, When accessing a government website. The result is that one of the biggest problems of the sites is linked to the lack of objectivity and use of easy-to-understand nomenclatures, which harms all the functionality of the site, since it is an issue which concerns all the requirements proposed by the Access to Information Law.